Analisis Keterampilan Komunikasi pada Mata Pelajaran IPAS Menggunakan Media Flipbook di Kelas IV SDN Jegulo I - Sa'diyah, Halimatus; Darmawan, Puguh (FKIP Unirow Tuban, 2024)
This study aims to analyze the communication skills of teachers and students in the subject of Social Studies (IPAS) using flipbook media in fourth-grade at SDN Jegulo 1. Effective communication skills among teachers in delivering complex IPAS concepts such as changes in substance and form are crucial for enhancing student comprehension. The research employs a qualitative approach with direct observation and in-depth interviews with IPAS teachers and students involved in the use of flipbook media. Data collected are analyzed to evaluate how flipbook media influences communicative interactions between teachers and students, as well as its impact on student understanding of IPAS content. Findings indicate that the use of flipbook media positively affects teachers' communication skills in presenting IPAS concepts visually and engagingly. Furthermore, this media enhances active student participation in the learning process by providing opportunities for creative interaction and responsiveness to the presented materials. In conclusion, integrating flipbook media in IPAS education at SDN Jegulo 1 effectively enhances communication skills from both teacher and student perspectives. This study recommends further development in utilizing visual media in teaching to support more dynamic and interactive learning environments in the future. Keywords: Communication skills, IPAS teachers and students, flipbook media, elementary education